Face Mask-Related Skin Conditions and Microbial Findings Among University Students During the COVID-19 Pandemic - Güran, Mümtaz (My University, 2026)
OBJECTIVE: Face masks are essential for disease prevention. However, prolonged use raises dermatological concerns. Addressing these issues can help develop guidelines that minimize risks and enhance comfort and adherence as a public health measure during future outbreaks. This study aimed to evaluate dermatological problems and pathogens related to face mask usage during the COVID-19 pandemic. METHODS: Data were collected through a structured questionnaire covering demographics, face mask usage habits, knowledge of mask use, and dermatological health. A pilot study was conducted to assess the questionnaire's reliability and validity. Microbiological samples were taken from participants' cheeks under the mask to identify common skin pathogens. Biostatistical methods were used to analyze the data. RESULTS: Dermatological problems, particularly acne and allergies, increased significantly during the pandemic, especially among surgical mask users. A notable rise in the prevalence of various bacteria and yeasts was observed in the samples. Knowledge of proper face mask usage was generally poor, with 81.1% of participants falling into poor/very poor categories. Surgical masks were used by 58.3% of participants, followed by cloth masks (33.1%) and KN95/N95 masks (8.7%). Most participants wore single-layer masks (70.9%), with 25.2% also using face shields. Female participants wore masks for significantly longer durations than males ( P = .04), whereas cloth mask users wore them for significantly shorter periods, regardless of sex ( P = .045). CONCLUSIONS: Prolonged face mask use is associated with increased dermatological issues and growth of skin pathogens. These findings underscore the need for promoting proper mask use, improving knowledge, and addressing skin care needs for future health emergencies. © © 2025 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: covering; COVID-19; face mask; face shield; pandemic; skin infection